Conceptual insights on factors shaping takaful technology (takatech) adoption in Malaysia - Haneffa Muchlis Gazali; Md Mahmudul Haque; Syahiru Shafiai; Norazidah Shamsudin; Syarah Syahira Mohd Yusoff (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2023)
The takaful and insurance industry is profoundly transformed, driven by rapid advancements in digital technology and the Internet of Things (IoT). While InsurTech has revolutionised traditional insurance practices, the acceptance of Takaful Technology (TakaTech) among consumers in Malaysia remains uncertain. This study aims to investigate the determinants of TakaTech adoption, focusing on attitude, subjective norm, relative benefit, and FinTech knowledge. The research is grounded in an extensive literature review and a conceptual framework analysis, drawing from an established Theory of Reasoned Action with relative benefit and Fintech knowledge. This study contributes to understanding consumer behaviour in the takaful industry, addressing a notable gap in current research. The identified determinants offer a detailed comprehension that can guide policymakers and market participants in refining marketing tactics. Takaful companies, armed with insights into customer viewpoints, can strategically promote products, increase market share, and expand commercial operations. It is essential to acknowledge the study's limitations. The conceptual nature precludes the establishment of causal linkages, and the proposed elements are derived from theoretical frameworks. Practical implications include the potential improvement of marketing efforts by tailoring strategies to customer preferences, thereby fostering TakaTech adoption. In conclusion, this research lays the groundwork for future empirical studies in the relatively unexplored field of Takaful Technology. Subsequent inquiries should examine additional factors and provide empirical evidence to authenticate the proposed conceptual framework. These efforts are vital for advancing knowledge in the expanding field of Takaful Technology, promoting continuous growth and innovation within the takaful industry.